Las gramáticas castellanas para extranjeros a lo largo del siglo XVI - Maquieira Rodríguez, Marina A. (Contextos, 1993)
During the 16th c, the appearance of the first treatises of Spanish for native speakers coincided with the emergence of the first textbooks for the teaching of Spanish for foreigners. Of course, they show different ways of systematizing and presenting grammatical contents. The aim of this article is to analyze the different approaches of both groups of texts, from the point of view of the treatises for foreigners, and to underline a certain degree of evolution in the techniques used within that framework.